2000
DOI: 10.1590/s0074-02762000000600026
|View full text |Cite
|
Sign up to set email alerts
|

Temporal change of the aggregation response in Triatoma infestans

Abstract: Adults and larvae of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 9 publications
0
14
0
1
Order By: Relevance
“…After 50 min of collection, the impregnated papers were immediately removed and maintained in a chamber at 28°C and 60-70% R.H. The filter papers with faeces were used six days after being collected, taking into account the data reported by Lorenzo Figueiras and Lazzari (2000).…”
Section: Methodsmentioning
confidence: 99%
“…After 50 min of collection, the impregnated papers were immediately removed and maintained in a chamber at 28°C and 60-70% R.H. The filter papers with faeces were used six days after being collected, taking into account the data reported by Lorenzo Figueiras and Lazzari (2000).…”
Section: Methodsmentioning
confidence: 99%
“…2C, D, E, F, 3A). This result is not less than surprising, as these bugs have proven to have one or more biological clocks controlling many of their activities (Ampleford & Steel 1982, Constantinou 1984, Ampleford and Davey 1989, Lazzari 1991, 1992, Reisenman et al 1998, Lorenzo Figueiras & Lazzari 2000, Minoli & Lazzari 2003, Barrozo et al 2004a). Circadian control of behaviour provides animals a temporal orientation independently from environmental cues for the occupation of temporal niches or in the co-ordination of activities between individuals and species (Aschoff 1989).…”
Section: Discussionmentioning
confidence: 89%
“…All previous instars were fed once a week on live hens, and once they become 5th instar larvae were maintained unfed for 10-20 days before being used in the experiments. This starvation level was selected as Lorenzo Figueiras and Lazzari (2000) showed that only after eight days after feeding bugs began to aggregate around dry faeces.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the intestinal symbionts of the triatomines, much emphasis has been given to Rhodococcus rhodnii (Goodfellow & Alderson) for its possible use as a strategy to reduce vectorial competence in these insects (Hurwitz et al 2012); however, there are other microorganisms that have been isolated from the middle intestine of R. prolixus, like the bacteria of the genera Streptococcus, Staphylococcus, Corynebacterum, Mycobacterium, Pseudomonas, and Escherichia (Douglas and Beard 1996). The quick processing of the enormous volume of ingested blood, by means of excretion of large quantities of water and salts as well as the gregarious behavior of the triatomines facilitates the transmission of symbionts among conspecifics (Figueiras and Lazzari 2000;Kollien et al 2001). …”
Section: Mutualist Microorganismsmentioning
confidence: 99%